Interactions Between Gut Microbiota and Campylobacter jejuni in Broiler Chickens: Insights for Health and Disease Control - Mohammed Salih Obaid Al-Mansouri (Journal of Applied Veterinary Science And Technology, 2026)
Background: Fundamental role in maintaining intestinal homeostasis, nutrient metabolism, and immune competence is played by the gut microbiota of broiler chickens. Although Campylobacter jejuni asymptomatically colonizes the chicken ceca, a significant threat to public health is posed through contaminated poultry products, necessitating a deeper understanding of the complex interplay between the microbiota and this zoonotic pathogen. Purpose: In the sized in this review is the current knowledge on the bidirectional interactions between the broiler gut microbiota and C. jejuni, focusing on microbial community dynamics, pathogen colonization, and potential intervention strategies. Review: Examined within this review are the composition and succession of gut microbiota, the impact of C. jejuni on microbial communities, and mechanisms such as nutrient competition, antimicrobial compound production, and immune modulation. Critically evaluated are microbiota based interventions, including specific probiotic strains (Lactobacillus and Bacillus spp.), prebiotics, and Fecal Microbiota Transplantation (FMT). Furthermore, special attention is directed toward recent advances from 2023–2025, specifically regarding genetically engineered probiotics and the role of environmental factors like mycotoxins in exacerbating colonization. Case Management: Ethical oversight regulations do not apply to this review since the core methodology relies on data synthesis from peer reviewed evidence without direct animal intervention conversely, practical field applications such as targeted probiotic administration and strict biosecurity guidelines are comprehensively analyzed. Conclusion: Identified as a key determinant in resisting C. jejuni colonization is a resilient and diverse gut microbiota. While harnessing the microbiome offers a sustainable, antibiotic free approach to food safety, further research is required to optimize these strategies for commercial conditions and to address knowledge gaps regarding strain specific efficacy.